Human MG-63 osteosarcoma cells responses to long and short term hyper- and hypothermia stress - Mohammed Ali, Nashiry; AL-Khateeb, Alyaa R; Yeap, S Keong; Froemming, Gabriele R A (Penerbit UTM Press, 2020)
Hyper- and hypothermia are utilized as treatment modalities in cancer treatment or as a protection against ischemia-reperfusion induced cell damage. The under-lying mechanism of hyper- and hypothermia, on cell death in osteosarcoma cells are not well understood. The aim of this study is to investigate the short- and long-term effects of various severities of hyper- and hypothermia on osteoblast-like osteosarcoma cells (MG-63). MG-63 cells were treated with mild and severe hyper- and hypothermia for short, medium and long-term periods. Severe hypothermia and hyperthermia showed a time-dependent toxicity; hence viability was reduced in a significant manner at all time points and the cells were undergoing apoptosis. Mild hypothermia, on the other hand, showed a protective effect and long term exposure increased the cell viability. Severe hyperthermia induced significant DNA damage at all time points. Caspase 3/7 activity showed a significant increase at 1 h of severe hyperthermia and 72 h of severe hypothermia (p<0.05). Hsp90 expression was significantly increased at 72 h of mild hyperthermia (p<0.01), whereas Hsp70 showed a significant increase after 24 and 72 h (p<0.01 and p<0.001). Hsp27 mRNA was increased significantly at 24 h only under mild hyperthermia (p<0.01). In conclusion, hyperthermia especially severe hyperthermia induced cellular stress in MG-63 cells leading to apoptosis. Hypothermia, on the other hand caused severe cell stress only when the cells were challenged for a prolonged period with severe low temperatures.